Does an Algorithm Replace Clinical and Sports Judgment in Exercise Prescription? - Jhony Jairo Cárdenas Garay; Carlos Alberto Romero Cuestas; Brian Johan Bustos Viviescas (Revista Finlay)
Artificial intelligence presents itself as a facilitator of connections, but it is not, in fact, a facilitator of specialized knowledge spaces. ChatGPT has democratized information, allowing general recommendations to be applied in communities with limited access. Its effectiveness depends on the training process. The irreplaceable value of clinical and sports judgment, physical therapy, and physical exercise require periodic assessments and individualized adjustments, impossible to imitate with artificial intelligence. Blind trust and overuse pose an imminent risk. Research warns that the advice given by artificial intelligence must be validated, as failures in rehabilitation can worsen injuries.